Sex Differences in Vagus Nerve Stimulation Effects on Rat Cardiovascular and Immune Systems - Yaghouby, Farid; Jang, Kee; Hoang, Uyen; Asgari, Sepideh; Vasudevan, Srikanth (Frontiers in Neuroscience, 2020)
Background: Investigations into the benefits of Vagus nerve stimulation (VNS) through clinical and pre-clinical research have led to promising findings for treating several disorders. Despite proven efficacy of VNS on approved conditions such as epilepsy and depression, underlying mechanism for off-target effects and contribution of factors such as sex differences can be beneficial to optimize the design of the therapy. New methods: In this paper, we assessed longitudinal effects of VNS on cardiovascular and immune systems and potential sex differences using rat models of long-term VNS. Rats were implanted with cuff electrodes around the left cervical vagus nerve for VNS and wireless physiological monitoring devices for continuous monitoring of cardiovascular system using electrocardiogram (ECG) signals. ECG morphology and heart rate variability (HRV) features were extracted to assess the cardiovascular changes by VNS in short-term and long-term timescales. We also assessed VNS effects on expression of inflammatory cytokines in blood during the course of the experiment. Statistical analysis was performed to compare results between male and female animals from Treatment and Sham groups. Results: Considerable differences between male and female rats in cardiovascular effects of VNS were observed as multiple cardiovascular features. However, the effects seemed to be transient with approximate one hour recovery after VNS. While short-term cardiovascular effects were mainly observed in male rats, females in general showed more significant long-term effects even after VNS stopped. We did not observe notable changes or sex differences in systemic cytokine levels by VNS. Comparison with existing methods: Compared to existing methods, our study design incorporated sex differences using wireless physiological monitoring and systemic blood cytokine levels along with long-term VNS experiments in unanesthetized rats. Conclusion: The contribution of sex differences for long-term VNS off-target effects on cardiovascular and immune systems was assessed using awake behaving rats. Although VNS did not change concentration of inflammatory biomarkers in systemic circulation for male and female rats, we observed significant differences in cardiovascular effects of VNS characterized using ECG morphology and HRV analyses.